8(2x-4)=2(8x+9)

Simple and best practice solution for 8(2x-4)=2(8x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(2x-4)=2(8x+9) equation:


Simplifying
8(2x + -4) = 2(8x + 9)

Reorder the terms:
8(-4 + 2x) = 2(8x + 9)
(-4 * 8 + 2x * 8) = 2(8x + 9)
(-32 + 16x) = 2(8x + 9)

Reorder the terms:
-32 + 16x = 2(9 + 8x)
-32 + 16x = (9 * 2 + 8x * 2)
-32 + 16x = (18 + 16x)

Add '-16x' to each side of the equation.
-32 + 16x + -16x = 18 + 16x + -16x

Combine like terms: 16x + -16x = 0
-32 + 0 = 18 + 16x + -16x
-32 = 18 + 16x + -16x

Combine like terms: 16x + -16x = 0
-32 = 18 + 0
-32 = 18

Solving
-32 = 18

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4x-36=-36+4x | | 3x=6x-1 | | 56+12n=80+8n | | 2+2n-6n=-6 | | 16x-(4-5x)=67 | | 6y=2x+6 | | 0.2x-8=x+4 | | 5-1(x-4)=3(x+2) | | 3x-4(5-2x)=2x-(3x-9) | | 10x=9x+19 | | 4(2z)=-72 | | 6x^2+54x=0 | | 2(x+3)(x-1)=x+176 | | x^3-0.9x^2-3.22x=0 | | -6a^2-7a+24=0 | | -5-4x=-13 | | -10m+6m=18-30 | | 2n=8n+21 | | 4+15r-3=9r+27-7r | | 3x-(5x+2)=9x-13 | | 5(4-2x)=100 | | w(w+4)=116 | | 0=-12n | | 8-12c=2 | | -4y^2+11y-6=0 | | r=-0.9233 | | 3t+5t=47+11-18 | | -5x+2+x+5=-5(x+2)+19 | | r^2=-0.923 | | 4x-5=6x+7 | | 6-6=4r-2r | | x^2-1.1x-2.76=0 |

Equations solver categories